RESEARCHING MORAL AND CITIZENSHIP EDUCATION IN MALAYSIA: PERSONAL REFLECTIONS ON THE ISSUE OF IMPARTIALITY IN DOING PHILOSOPHICAL RESEARCH ON PLURALISM - Nur Surayyah Madhubala Abdullah (Sosio-Didaktika: Social Science Education Journal, 2016)
AbstractIn the process of conducting a philosophical examination on the conceptualization of pluralism within moral and citizenship education in Malaysia, I was faced with an ethical issue about impartiality.  This article considers this issue in the context of my research through my reflections and what I learnt from them about conducting philosophical research on complex and controversial concepts. This article describes issues I faced in my research and the understanding I gained about researching complex and controversial topics in philosophical and other research. It goes on to suggest how addressing this issue in the research process provided an opportunity for myself as a researcher to obtain reflective positioning on the issue of research on such topics. The paper concludes that such positioning provides a reason for researcher to take a more communicative stand when researching topics of a similar nature to obtain a proper understanding of a concept within their research. AbstrakDi dalam proses penelitian filosofis terhadap konseptualisasi pluralisme dalam pendidikan moral dan kewarganegaraan di Malaysia, peneliti dihadapkan pada isu-isu etis tentang imparsialitas. Artikel ini menyoroti isu-isu etis tentang imparsialitas dalam konteks penelitian, melalui refleksi pribadi dan apa yang saya pelajari dari hal-hal itu mengenai pelaksanaan penelitian filosofis dalam konsep yang kompleks dan kontroversial. Artikel ini menjelaskan isu yang saya hadapi di dalam penelitian saya dan pemahaman yang saya dapatkan menyangkut penelitian yang bertopik kompleks dan kontroversial dalam aspek filosofis. Artikel ini menyarankan bagaimana cara menangani masalah-masalah yang berhubungan dengan isu-isu etis tentang imparsialitas melalui proses penelitian sehingga memberi kesempatan untuk mendapatkan posisi reflektif pada isu penelitian tersebut. Artikel ini menyimpulkan bahwa posisi tersebut memberikan alasan bagi peneliti untuk mengambil sikap lebih komunikatif ketika meneliti topik yang serupa guna mendapatkan pemahaman yang tepat.Pengutipan: Abdullah, N. S. M. (2016). Researching Moral and Citizenship Education in Malaysia: Personal Reflection on the Issue of Impartiality in Doing Philosophical Research on Pluralism. SOSIO DIDAKTIKA: Social Science Education Journal, 3(2), 2016, 105-114. doi:10.15408/sd.v3i2.4472.Permalink/DOI: http://dx.doi.org/10.15408/sd.v3i2.4472